Seeking the Shore: Evidence for Active Submarine Canyon Head Incision Due to Coarse Sediment Supply and Focusing of Wave Energy. Issue 22 (26th November 2018) - Smith, M. Elliot; Werner, Samuel H.; Buscombe, Daniel; Finnegan, Noah J.; Sumner, Esther J.; Mueller, Erich R.
Abstract: Submarine flows carve canyons into continental shelves, yet the conditions and events responsible for canyon incision are incompletely understood. Coarse sediment flux has been shown to promote terrestrial bedrock incision via abrasion in rivers, but similar processes in submarine canyons have yet to be systematically documented. We use repeat bathymetry, provenance analysis, wave modeling, and channel network analysis to show that longshore sheltering and wave focusing by the Delgada submarine canyon induce sediment accumulation and elevated wave shear stresses in its headwall region that frequently mobilize coarse bed material. These mobilizations scour bedrock in the headwall and generate abrasive turbidity currents that work to carve the canyon's active channel into bedrock. These findings highlight an important positive feedback between submarine canyons, waves, and sediment supply and suggest that submarine canyons adjacent to wave‐dominated, coarse sediment‐rich coastlines seek the shoreline through headward incision. Plain Language Summary: The carving of submarine canyons into the continental shelf is poorly understood relative to river valleys on land. We studied a submarine canyon in Northern California that is connected through littoral transport to river sediment using a combination of seafloor mapping, tracking sediments using their chemical elements, and simulating waves and currents to better understand which processes are responsible for canyon erosion. Our findings suggest that canyon focusing of wave energy and an abundant supply of coarse sediment cause erosion at the canyon's head. This finding helps explain why submarine canyon channel networks erode toward shore and predicts that canyons near mountain ranges will preferentially remain connected the shoreline. Key Points: Repeat sonar surveys and sedimentary provenance document sediment transport and erosion in Delgada submarine canyon, Northern California Hydrodynamic modeling and littoral budgets suggest that coarse sediment is mobilized by waves in the canyon head, triggering turbidity currents Sediment supply and wave focusing promote erosion of submarine canyons along tectonic coasts, encouraging littoral to deep sea connectivity